Good practices in early childhood education: Looking at early educators' perspectives in six European countries - Gregoriadis, Αthanasios (2016)
The 21st century has been described by many researchers as an era of educational change. The constantly evolving smart technologies, the Internet and the ICTs claim a substantial part of teachers’ and children’s daily time, interest and practices. It is true that the change that has occurred in education practice and tools over the last fifteen years has been truly remarkable. Theoretical frameworks like constructivism, sociocultural theory, attachment theory and others, have enhanced the way we approach children’s learning and development. The traditional face-to-face and teacher-centered approaches have being substituted by discovery learning, individualized learning, creative thinking, hand on experiences and child centered practices. The recent reforms in several early childhood curriculums of the international educational community have highlighted the demand to develop learning environments that will meet children’s needs in the most effective way (Gettinger, 2003). But what constitutes a high quality early childhood education environment? What are the basic requirements for an early childhood education environment in order to be described as qualitative? Despite the technological advances and the shift of educational interest towards children’s needs, abilities and motivation, the fact remains that there are some classic and global criteria that must be met for an early childhood environment to be characterized as qualitative. Harms, Clifford and Cryer (2005) mention that in order to provide quality of life care and education, we must provide for the three basic needs all children have: (a) Protection of their health and safety, (b) Building positive relationships and classroom climate, and (c) Opportunities for stimulation and learning from experience.